Computing the environment : digital design tools for simulation and visualisation of sustainable architecture - Peters, Brady; Peters, Terri (Chichester, West Sussex, UK : Wiley, 2018)
Computing the Environment presents practical workflows and guidance for designers to get feedback on their design using digital design tools on environmental performance. Starting with an extensive state-of-the-art survey of what top international offices are currently using in their design projects, this book presents detailed descriptions of the tools, algorithms, and workflows used and discusses the theories that underlie these methods. Project examples from Transsolar Klimaengineering, Buro Happolds SMART Group, Behnish Behnisch Architects, Thomas Herzog, Autodesk Research are contextualized with quotes and references to key thinkers in this field such as Eric Winsberg, Andrew Marsh, Michelle Addington and Ali Malkawi.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 22, 2018).
Keywords: Building information modeling; Building -- Technological innovations; Architecture -- Technological innovations; TECHNOLOGY & ENGINEERING -- Engineering (General); ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- Landmarks & Monuments; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Reference; Architecture -- Technological innovations; Building information modeling; Building -- Technological innovations; Electronic books